Workplace gaslighting: Conceptualization, development, and validation of a scale - Kukreja, Priyam; Pandey, Jatin (Frontiers in Psychology, 2023)
Introduction Gaslighting is a form of abuse that has transgressed the realms of romantic relationships to the relationships at work. Despite the growing literature on abuse at work, the conceptualization and measurement of gaslighting at work have received scarce attention. The study aimed to address this existing lacuna in the literature by conceptualizing and developing a measure of gaslighting at work. Methods By drawing upon and integrating existing works of literature on harmful leader behaviors, workplace abuse, and workplace mistreatment, the authors have conceptualized the concept of gaslighting in a new context, i.e., work settings, and delineated its dimensions and conceptual boundaries. Among three different samples (total N = 679) of employees, the study developed a new 12-item measure of gaslighting in work relationships, the Gaslighting at Work Questionnaire (GWQ). The study further tested the psychometric properties of GWQ, namely, internal consistency, face, and construct validity of GWQ. Additionally, a time-lagged study was used to validate the scale within a nomological net of conceptual relationships. Results Exploratory and confirmatory factor analysis supported a two-dimensional structure of gaslighting at work (trivialization and affliction). The psychometric properties of GWQ were established. Finally, using a time-lagged study, the scale was validated within a nomological net of conceptual relationships by showing the relationship of gaslighting at work with role conflict and job satisfaction. Discussion The GWQ scale offers new opportunities to understand and measure gaslighting behaviors of a supervisor toward their subordinates in the work context. It adds to the existing literature on harmful leader behaviors, workplace abuse, and mistreatment by highlighting the importance of identifying and measuring gaslighting at work.